2010
DOI: 10.1016/j.preteyeres.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel aspects of corneal angiogenic and lymphangiogenic privilege

Abstract: In this article, we provide the results of experimental studies demonstrating that corneal avascularity is an active process involving the production of anti-angiogenic factors, which counterbalance the proangiogenic/lymphangiogenic factors that are upregulated during wound healing. We also summarize pertinent published reports regarding corneal neovascularization (NV), corneal lymphangiogenesis and corneal angiogenic/lymphangiogenic privilege. We outline the clinical causes of corneal NV, and discuss the angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 364 publications
5
155
0
10
Order By: Relevance
“…In these groups, intensity of the vasculature varied between 2 and 3 until the end of evaluation period, while the control group did not exceed grade 1, returning to 0 from 33 rd day. According to Ellenberg et al (2010), corneal vascularization is expected whenever lesion reaches stroma or deeper layers of the cornea; this is an important way of carrying cells and inflammatory mediators required for the repair process. As in this work, Macedo et al (2010) observed highest degree of vascularization between 15 and 48 days when applying bacterial cellulose (BC) to cover ulcers in rabbits' corneas.…”
Section: Resultsmentioning
confidence: 99%
“…In these groups, intensity of the vasculature varied between 2 and 3 until the end of evaluation period, while the control group did not exceed grade 1, returning to 0 from 33 rd day. According to Ellenberg et al (2010), corneal vascularization is expected whenever lesion reaches stroma or deeper layers of the cornea; this is an important way of carrying cells and inflammatory mediators required for the repair process. As in this work, Macedo et al (2010) observed highest degree of vascularization between 15 and 48 days when applying bacterial cellulose (BC) to cover ulcers in rabbits' corneas.…”
Section: Resultsmentioning
confidence: 99%
“…In normal corneas, angiogenesis is controlled by two counterbalancing systems: proangiogenic factors (vascular endothelial growth factor [VEGF], basic fibroblast growth factor, matrix metalloproteinases, integrins, and cytokines) and antiangiogenic factors (pigment epithelium-derived factor, VEGFR3, soluble VEGFR-1, angiostatin, and endostatin) (19,20). Antiangiogenic therapy may prove a promising direction to reduce graft failure (21).…”
mentioning
confidence: 99%
“…Factors with antiangiogenic properties include endostatin, angiostatin, thrombospondin, pigment epithelium-derived factor, and others. 19 Their balance is actively maintained, as exemplified by Many of these factors have also been found to have a role in ocular and, more specifically, corneal neovascularisation. Angiopoietin-1 binds to endothelial Tie-2 receptors to stabilise the established vasculature.…”
Section: Corneal Avascularity Is the Results Of An Active Regulatory Pmentioning
confidence: 99%
“…75 On top of their anti-inflammatory properties, steroids have been shown to inhibit proliferation and migration of vascular ECs. 19 Using a rodent model to compare anti-lymphangiogenic effects of different topically applied corticosteroids, the strongest effect was measured for prednisolone, which may therefore render this substance particularly suitable to 87 prevent rejection of corneal allografts. 76 However, side effects of steroids are an important cause of ocular complications, whereas efficacy in cases of noninflammatory-mediated corneal neovascularisation is limited.…”
Section: Antiangiogenic Factors In the Corneamentioning
confidence: 99%